2021
DOI: 10.1111/acel.13485
|View full text |Cite
|
Sign up to set email alerts
|

miR‐195‐3p alleviates homocysteine‐mediated atherosclerosis by targeting IL‐31 through its epigenetics modifications

Abstract: Atherosclerosis is a serious age‐related disease, which has a tremendous impact on health care globally. Macrophage inflammation is crucial for the initiation and progression of atherosclerosis, and microRNAs (miRNAs) recently have emerged as potent modulators of inflammation, while the underlying mechanisms of its involvement in homocysteine (Hcy)‐mediated macrophage inflammation of atherosclerosis remain largely unknown. Here, we demonstrated that elevated Hcy inhibits the expression of miR‐195‐3p, which in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Recently, advances have shown that increased Hcy in serum level is a primary cause of cardiovascular diseases, diabetes, neurodegenerative diseases, and so on. Hcy was also involved in the initiation and progression of atherosclerosis by inhibiting the expression of miR-195-3p and in turn, enhancing the inflammation through IL-31 ( 21 ). In cardiovascular diseases, Hcy was reported to cause endothelial dysfunction through ENaC, or the toxicity related to iron containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, advances have shown that increased Hcy in serum level is a primary cause of cardiovascular diseases, diabetes, neurodegenerative diseases, and so on. Hcy was also involved in the initiation and progression of atherosclerosis by inhibiting the expression of miR-195-3p and in turn, enhancing the inflammation through IL-31 ( 21 ). In cardiovascular diseases, Hcy was reported to cause endothelial dysfunction through ENaC, or the toxicity related to iron containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that chronic progressive inflammation has deleterious and additive effects that accelerate AS and contribute to lesion rupture [ 31 ]. HHcy promotes pro-inflammatory cytokine production and lipid accumulation in macrophages and has been regarded as a major driving force in the development of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia can lead to elevated inflammatory factors in blood vessels, damage to the vascular endothelium, and proliferation of vascular smooth muscle cells ( 31 , 32 ). High homocysteine has been reported to promote atherosclerosis and increase the risk of ischemic strokes ( 11 , 33 , 34 ). Because mechanisms such as inflammation are involved in the formation and rupture of IAs, pathological changes caused by homocysteine may contribute to their formation and rupture.…”
Section: Discussionmentioning
confidence: 99%